Polishing for glass ceramics: Which protocol? - Silva, Tania Mara da [UNESP]; Rodrigues Danzi Salvia, Ana Carolina [UNESP]; Carvalho, Rodrigo Furtado de [UNESP]; Pagani, Clovis [UNESP]; Rocha, Daniel Maranha da; Silva, Eduardo Galera da [UNESP] (Elsevier B.V., 2014)
Purpose: The execution of adjustments on ceramic restorations is sometimes necessary for either correction of occlusion and/or inadequate contours or esthetical improvements. Clinically, the surfaces undergo weariness through fine grinding diamond burs which remove the superficial glazing layer. Several materials for ceramic polishing have been used in an attempt to reach a satisfactory surface smoothness. The aim of this study was to perform a literature review on different polishing protocols of several dental ceramics. Study selection: This is a literature review performed through scientific articles published between 2004 and 2012, indexed in MEDLINE, PubMed and Scielo databases. The study selected and analyzed a total of 20 relevant articles that evaluated different types of ceramics, polishing treatment and surface roughness.Results: After an extensive literature review, this study observed: 1 - after the rupture of the glazing layer due to the adjustments of the restorations, the best choice for the polishing of the surface will depend on the type of ceramics used; 2 - glazing procedure provide excellent results regarding to the superficial smoothness; however, if reglazing is impossible, either abrasive rubber cups/points or sandpaper discs followed by the use of diamond polishing pastes results in a satisfactory superficial smoothness; 3 - clinical studies that take into account the behavior of the protocols polishing are scarce and should be encouraged; 4 - the large number of variables influence the final outcome of polishing should be considered. Conclusions: The necessity in standardization of methodologies to enable a comparison among researches. (c) 2014 Japan Prosthodontic Society. Published by Elsevier Ireland. All rights reserved.
Keywords: Dental ceramics; Polishing methods; Superficial roughness